Depression and obstructive sleep apnea - Hobzova, Milada; Prasko, Jan; Vanek, Jakub; Ociskova, Marie; Genzor, Samuel; Holubova, Michaela; Grambal, Ales; Latalova, Klara (Neuro endocrinology letters, 2017)
OBJECTIVE: Obstructive sleep apnea (OSA), is described as intermittent interruptions or reductions in airflow which are initiated by an incomplete or complete collapse of the upper airways despite respiratory effort. When left untreated, OSA is connected with comorbid conditions, such as cardiovascular and metabolic illnesses. METHOD: The PubMed database was used to examine papers published until April 2017 using the subsequent terms: "obstructive sleep apnea" or "obstructive sleep apnoea" and "depression" in successive combination with "CPAP (continuous positive airway pressure)", "therapy", "pharmacotherapy", "psychotherapy", "cognitive behavioral therapy" or "quality of life". RESULTS: After assessment for the suitability, 126 articles were chosen. The numerous evidence of a connection between OSA and depressive symptoms, as well as depressive disorder, were found. This connection may be directly or indirectly linked due to the participation of some OSA mediators consequences such as obesity, hypertension, and the decreased quality of life. Patients with the comorbid major depression and OSA reported more severe and longer episodes of depression. Nevertheless, the information on the effect of the treatment of OSA using CPAP on the depressive symptoms was limited. Still, the current state of the art suggests that this treatment decreases the severity of the comorbid depressive symptoms. CONCLUSIONS: It is important to evaluate the symptoms of depression in the patients with OSA. On the other side, a psychiatrist should not just treat the depression, as it is also important to screen individuals at high risk of OSA when assessing patients for depressive disorder, especially those with depression resistant to treatment.
Keywords: Depressive Disorder; deprese; lidé; obstrukční spánková apnoe; Depression; depresivní poruchy; Sleep Apnea, Obstructive; Treatment Outcome; trvalý přetlak v dýchacích cestách; výsledek terapie; Continuous Positive Airway Pressure; Humans